ANTIMICROBIAL SECONDARY METABOLITES FROM SILENE RUBELLA GROWING IN EGYPT - Hussein, Ismail A.; Srivedavyasasri, Radhakrishnan; El-Hela, Atef A.; Mohammad, Abd-elsalam I.; Ross, Samir A. (Journal of Biomedical and Pharmaceutical Research, 2019)
Phytochemical investigation of the ethanolic extract of dried aerial part of Silene rubella led to the isolation of eighteen compounds (1 -18). The isolated compounds were identified by their NMR, and MS spectral data as ecdysterone (1), apigenin (2), diosmetin (3), kaempferol (4), luteolin (5), myricetin (6), quercetin (7), isovitexin (8), vicenin 2 (9) rutin (10), (R)-naringin & (S)-naringin (11 & 12), chlrogenic acid (13), betulinic acid (14), oleanolic acid (15), ursolic acid (16), D-pinitol (17), and spinasterol (18).This is the first report on isolation of chemical entities from this plant. Crude ethanolic extract of S. rubella, exhibited antimicrobial activity against Escherichia coli with IC50 48.85 μg/mL. Oleanolic acid (15) exhibited good activity against E. coli with IC50 15.78 μg/mL. Oleanolic acid (15) and betulinic acid (14) exhibited potent antibacterial activity against Vancomycin resistant Enterococcus (VRE), with IC50 6.36 and 7.51 µg/mL, respectively.Keywords: Silene rubella; antimicrobial; Vancomycin resistant Enterococcus (VRE); Escherichia coli (E. coli); Oleanolic acid; Betulinic acid